Antiviral Potential of Milk Proteins and Peptides against Zoonotic Viruses - Santos, Maria Isabel; Moita, Tomás; Pedroso, Laurentina; Lima, Ana (An Overview of Disease and Health Research Vol. 2, 2025)
In addition to its well-established nutritional value, milk is increasingly recognized as a rich source of bioactive compounds with potential health-promoting properties. Among these, milk proteins and their derived peptides have attracted growing scientific interest due to their multifunctional biological activities. Notably, recent studies have identified potent antiviral effects associated with these components, suggesting a promising role in the prevention and control of zoonotic viral diseases. Despite a growing body of research exploring milk’s broader bioactivities, the specific antiviral potential of milk-derived peptides remains relatively underexplored in the literature. This gap represents a critical opportunity to advance knowledge in the fields of virology, nutrition, and One Health, particularly in the context of emerging infectious diseases. This review aims to consolidate current scientific evidence on the antiviral properties of milk-derived proteins and peptides, with a particular focus on zoonotic viruses and the underlying mechanisms of action. To achieve this, a comprehensive literature search was conducted using scientific databases Relevant peer-reviewed articles published in English were identified through the application of specific keywords and Boolean operators. The selection process involved screening titles, abstracts, and full texts to ensure alignment with the scope of the review. These mechanisms may include inhibition of viral entry and attachment, interference with the replication processes, or direct viral inactivation through interactions with viral membranes. Given their broad-spectrum activity and favourable safety profile, milk-derived antiviral peptides represent a compelling area for further research and development. Their potential applications span human and veterinary medicine, the nutraceutical sector, and the dairy industry—especially in a post-pandemic world where innovative antiviral strategies are urgently needed.